O diretor escolar e as práticas de colaboração em construção na escola pública municipal de São Paulo - Lira, Patrícia de Souza (2022)
This research was motivated by concerns related to the daily management practices of the school principal, more specifically, related to collaborative practices. The last decades have shown a growing demand on improving the quality of education, and the role of a Principal has been playing an important part in this discussion. This professional is considered a key person who must lead educational projects and mobilize complex processes of creating didactic content and institutional change. Collaboration is shown to be a possible path to make school to go to that direction. The main objective is to investigate the collaborative practices of management in the school routine from the perspective of the Principal within the public school. The specific objectives are: (1) Understand whether or not and how collaborative initiatives are presented by school Principals to be incorporated as good work practices in schools; (2) Have a clear idea of the Principal's perspective regarding collaborative work related to school management; (3) Identify which aspects the school Principal recognizes as important to create collaborative practices; (4) Understand what are the elements that favor or not the creation of a collaborative environment in the management practices; (5) Identify the learning curve related to the Principal role and how this would impact the collaboration among school staff. Among the authors supporting this study, the following stand out with regard to school management and the role of a Principal: Libâneo (2008), Lück (2015) and Paro (2015)l; connect the leadership to the Principal's work :Flessa (2019), Fullan (2019) and Weinstein (2019); Hargreaves and O’Connor (2018) and Passos and André (2016) make up the framework with contributions on collaboration. This qualitative research has as participants four school Principals in the municipal network of São Paulo, recommended by teaching supervisors as professionals who follow collaborative practices. The data gathering was based on interviews with specific approach to direct questions to all involved in the process. Data analysis, based on Prose Analysis (ANDRÉ, 1983), that shows indications that Principals' practices have been changing, moving away from an authoritarian approach and being more progressive and collaborative influencing school staff in a positive way, inviting people to work in group to aim to find the best approach to reach the school goals. Evidence that leads us to characteristics such as actions based on shared goals and interests, taking into account a variety of work styles, shared and open dialogue, inputs and feedbacks, team work and with a sense of solidarity. Such things as collective spaces, the exchange of knowledge between different institutions, attitudes that embody respect and commitment imply to be facilitators for building collaboration between groups. The turnover and high workload appear as constraints that make it very difficult for collaboration to happen. Learning experienced by the Principals highlights inclusion practices, delegating tasks, learning from others, taking a stand without being harsh, being less individualistic, and a political shift in the progressive Direction